2009
DOI: 10.1902/jop.2009.090057
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Signals Mediated by Programmed Death‐1 Are Involved With T‐Cell Function in Chronic Periodontitis

Abstract: These data show that PD-1 engagement could be involved in the modulation of IFN-gamma production by T cells in patients with chronic periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 46 publications
0
12
0
1
Order By: Relevance
“…The role of CD8 + T‐cells in periodontitis has been analyzed in patients with different forms of periodontitis . CD8 + T‐cell clones from inflamed periodontal tissues were analyzed in early studies, by stimulation with phytohemagglutinin, for their production of different cytokines and their biological functions.…”
Section: Role Of Cytotoxic T‐cell Subsets In Periodontitismentioning
confidence: 99%
“…The role of CD8 + T‐cells in periodontitis has been analyzed in patients with different forms of periodontitis . CD8 + T‐cell clones from inflamed periodontal tissues were analyzed in early studies, by stimulation with phytohemagglutinin, for their production of different cytokines and their biological functions.…”
Section: Role Of Cytotoxic T‐cell Subsets In Periodontitismentioning
confidence: 99%
“…Earlier studies (do Vale et al, 2004;Figueira et al, 2009) showed that peripheral blood mononuclear cells from patients with periodontitis did not proliferate in response to bacterial antigens. However, other studies (Pejcic et al, 2011;Gaddale et al, 2014) have confirmed an increased number of WBCs and neutrophils in the peripheral blood of patients with moderate to severe periodontitis, with a positive correlation between disease severity and number of WBCs in the blood.…”
Section: Discussionmentioning
confidence: 99%
“…In gingival tissue from chronic periodontitis, a marked increase in total CD4 + T cells, CD8 + T cells, and B cells, akin to neutrophils, was observed, and most of the CD4 + T cells produced IL-17 ( 34 ). Although in the study of Dutzan et al CD8 + Treg are not detected in the gingiva of chronic periodontitis patients ( 34 ), previous studies showed that some gingival CD8 + T cells lack CD28 while expressing the inhibitory receptor PD1 ( 35 – 37 ). These features are associated with an effector–memory phenotype ( 20 ).…”
Section: Gingival Cd8 + T Cells and Chronic Periodmentioning
confidence: 93%
“…Given the effector–memory phenotype ( 34 37 ), and unlike CD4 + T cells that express CD28 and may respond to TCR/CD28-mediated signals, gingival CD8 + T cells may preferentially be activated in a TCR-independent manner by local signals produced during stress and/or injury, including a variety of endogenous products that signal through innate receptors, as discussed elsewhere ( 20 ). As a result, upon innate receptor triggering gingival CD8 + T cells may secrete cytokines, such as IL-10 and IFN-γ, reported to have bone repairing properties ( 23 , 26 ).…”
Section: Gingival Cd8 + T Cells: Molecular Signalsmentioning
confidence: 99%